Measuring User Readiness of Web-based Encyclopedia for Kids based on Technology Readiness Index - Gita Indah Marthasari; Nur Hayatin; Evi Dwi Wahyuni; Rellanti Diana Kristy (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Readiness level measurement of users who uses a new technology is needed to determine the success of technology to get a recommendation for further technology development. Technology Readiness Index (TRI) is a method to measure the user readiness level to a new technology. The approach is carried out by using the TRI method more personally, where measurements are made using four variables, i.e. optimism (optimism), innovativeness (innovation), discomfort (inconvenience), and insecurity (insecurity). This method will be implemented to the Anapedia application. Anapedia is a new technology of open web-based encyclopedia for children that is still needs developing and testing. Data collection in this study was carried out using a questionnaire research instrument that distributed to students and teachers in an elementary school. From the measurement of the level of readiness of users taken from 108 respondents, it was found that the level of readiness of Anapedia users was at a high technology readiness with value of 3.63